PASTORAL CARE FOR CHRISTIAN YOUTH IN PREPARATION FOR MARRIAGE USING EFFECTIVE CBT METHODS (AARON BECK) AND THE VALUE-SEMANTIC ORIENTATION OF CLASSICAL BIBLICAL COUNSELING (JAY ADAMS) - Fakhrutdinova, Ekaterina (SWorldJournal, 2025)
The article addresses the pastoral care for Christian youth during marriage preparation using effective cognitive behavioral therapy (CBT) methods developed by Aaron Beck and the value-semantic orientation of classical biblical counseling by Jay Adams. Th